PENENTUAN PRIORITAS WILAYAH KERJA UNTUK PENINGKATAN PENGAWASAN PERIKANAN DI WPP NRI 711 (Priority Determination of Working Area For Surveillance Improvement in Indonesia Fisheries Management Area 711 (WPP NRI 711)) - Yaser Krisnafi; Budhi Hascaryo Iskandar; Sugeng Hari Wisudo; John Haluan (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2017)
ABSTRACTThe Fisheries Management Area of Republic Indonesia or often abbreviated as WPP-NRI is a fisheries management area for fishing, conservation, research and fisheries development covering inland waters, archipelagic waters, territorial sea, additional zones and the Exclusive Economic Zone of Indonesia (ZEEI). Priority of selection work unit surveillance as the base pier becomes something very important because the pier of the surveillance vessel becomes a major requirement. The base pier is not just a place to moor the vessel but the base pier becomes a function of ongoing surveillance operations. In this case the facilities and facilities of the base pier should be able to provide facilities as well as ease in supporting surveillance operations activities.Problem in selection of prioritization unit of work is a complex problem, it needs a method to overcome them.TOPSIS is one of decision making method capable for solving the problem of multi-criteria, TOPSIS working principle is the chosen alternative should have the closest distance from the positive ideal solution and the farthest from the most negative solution.The result of testing on 11 alternatives in 6 criteria showed that development priority area for fisheries surveillance work units in WPP NRI 711 were: Batam (score 0,672) work unit Pontianak (score 0,671), and Natuna (score 0,647).The results of the ranking are to be used as a reference for determining the improvement surveillance strategy and to minimize losses due to illegal fishing of the natural resources in the region of WPP NRI711 in Indonesia.Keywords: TOPSIS, work unit, WPP NRI 711ABSTRAKWilayah Pengelolaan Perikanan Negara Republik Indonesia atau sering disingkat dengan WPP NRI merupakan wilayah pengelolaan perikanan untuk penangkapan ikan, konservasi, penelitian, dan pengembangan perikanan yang meliputi perairan pedalaman, perairan kepulauan, laut teritorial, zona tambahan, dan Zona Ekonomi Ekslusif Indonesia (ZEEI). Prioritas pemilihan UPT Pengawasan SDKP (Sumber Daya Kelautan dan Perikanan) sebagai dermaga pangkalan menjadi sesuatu yang sangat penting dikarenakan dermaga kapal pengawas menjadi suatu kebutuhan yang paling utama. Dermaga pangkalan bukan hanya sebatas tempat untuk tambat kapal saja melainkan dermaga pangkalan menjadi sebuah fungsi berlangsungnya kegiatan operasi pengawasan. Dalam hal ini adalah sarana dan fasilitas dermaga pangkalan harus mampu memberikan fasilitas serta kemudahan dalam mendukung kegiatan operasi pengawasan. Permasalahan penentuan prioritas pemilihan satker merupakan masalah yang komplek maka diperlukan suatu metode untuk membantu mengatasinya. TOPSIS adalah metode pengambilan keputusan yang mampu menyelesaikan masalah multi-criteria. Prinsip kerja TOPSIS adalah alternatif yang dipilih harus memiliki jarak terdekat dari solusi ideal positif dan terjauh dari solusi ideal negatif. Dari pengujian 11 alternatif dari 6 kriteria didapatkan prioritas pengembangan satuan kerja wilayah pengawasan perikanan di WPP 711 adalah: Satker Batam = 0,672; Satker Pontianak = 0,671 dan Satker Natuna = 0,647. Hasil perangkingan tersebut akan dijadikan acuan sebagai dasar penentuan strategi peningkatan pengawasanwilayah perikanan di WPP 711 sehingga mampu meminimalisasi kerugian negara akibat pencurian SDA di wilayah WPP 711 Indonesia.Kata kunci: TOPSIS, unit kerja, , WPP NRI 711